Metaphysics : book [theta] - Aristotle; Makin, Stephen, 1955- (Oxford : Clarendon Press ; New York : Oxford University Press, 2006)
"This addition to the Clarendon Aristotle series comprises a new translation of Aristotle's Metaphysics Book [Theta], an introduction to the basic notions and problems around which the book is structured, and a detailed chapter-by-chapter critical commentary. Makin's aim throughout is to present Aristotle's text in as accessible a manner as possible, and to encourage and enable readers to engage critically with Aristotle's arguments. Metaphysics Book [Theta] is an extended discussion of the distinction between the actual and the potential, a distinction which is important both for Aristotle's own thought and for later philosophers. Aristotle starts by considering the relation between capacities and changes, and then expands his discussion to cover the notions of matter and substance, which are at the heart of his ontology. Among the topics covered in detail in the commentary are the distinctions between two-way and one-way capacities, and between rational and non-rational capacities; arguments against reductive views of possibility and impossibility; Aristotle's treatment of capacity identity and his account of the exercise of capacities; Aristotle's answer to the question 'what is it to be potentially such and such?'; his defence of the idea that actuality is prior in various ways to potentiality; and his brief comments on the evaluation of potentialities and actualities, the role of the actual-potential distinction in geometrical knowledge, and his treatment of truth and falsity."--BOOK JACKET.
Includes bibliographical references (p. 274-279) and indexes.
Translated from the Ancient Greek.
committed to retain
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Metaphysics -- Early works to 1800.; Electronic books